Accelerated methods for solving grid equation I - A, Dang Quang (Journal of Computer Science and Cybernetics, 2016)
In this paper we propose a technique accelerating the convergence rate of the known iterative schemes for  solving grid equations such as the alternately triangular method and the alternating direction method. Our idea is by the parametric extrapolation of the solutions of equations, which can be solved faster than the original ones. The effeciancy of the accelerated methods is shown on example.